Pro Brasilia Fiant Eximia: Paulistanidade Impressa Em Livros Didáticos Aprovados No Estado De São Paulo (1911-1937)" - Abbeg, Valter Andre Jonathan Osvaldo [UNIFESP] (2018)
This Research Is Part Of The Set Of Studies On The History Of Textbooks. The Objective Is To Identify And Analyze The Elements Of Paulistanidade Printed In Graduated Series, Set Of Didactic Books, Approved By The State Of São Paulo For Use In Public Schools From 1911 To 1937. Starting From Theoretical Contributions Of Cultural History Articulating Conceptions Of Nation (Hobsbawm) , Social Imaginary (Veyne And Castoriadis) And Image (Aumont And Joly). Three Movements Were Used To Exemplify The Different Characteristics Of Paulistanidade: Separatism, Federalism And Nationalism; All Constituted In Public Speeches Published In Newspapers And Magazines From São Paulo. The Understanding Of Paulistanity Permeates The Political Discourses Of The Republican Paulista Party And Other Institutions And Movements That Have Added Intellectuals And Professionals, Be It The Historical And Geographical Institute Of São Paulo, The Modernist Movement (Which Had One Of Its Summits The Modern Art Week) , Or Even The Nationalist Le